Antistatic renewable plastic particles and processing method thereof
By using plastic particles of specific components and the preparation process, the problem of antistatic plastic decay in high temperature and humidity changing environments is solved, and high stability and renewable antistatic properties are achieved without affecting the recycling and recycling of plastics. use.
Patent Information
- Application Number
- CN202411553170.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2024-12-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The antistatic effect of existing antistatic plastics will decline in environments with high temperature and humidity changes, and the added antistatic agents affect the recycling and reuse of plastics, resulting in insufficient stability and renewability.
Plastic particles using components such as polyethylene, polypropylene, polyamide, octyl stearate, polycarbonate, antistatic agent, antioxidant, conductive filler, surfactant and conductive polymer are used through a specific preparation process and Processing method, renewable plastic particles with good antistatic properties and tensile strength are prepared.
The prepared plastic particles maintain good antistatic properties in an environment with high temperature and humidity changes. Due to the use of conductive fillers and conductive polymers, the accumulation of static electricity is effectively reduced and the antistatic properties are improved without affecting the recycling and recycling of plastics. use.
Smart Images

Figure BDA0005115619570000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of plastic particles, and more specifically to antistatic renewable plastic particles and a processing method thereof. Background Art
[0002] Plastic pellets, also known as plastic raw material pellets, are basic raw materials used in various plastic processing processes. They are small solid particles made from plastic raw materials (such as resin) through processes such as heating, mixing and cutting. The types, properties and application range of plastic pellets are very wide.
[0003] In some application scenarios, plastic products need to have certain antistatic properties. Antistatic plastics reduce the accumulation of surface static charges by adding antistatic agents or conductive fillers, thereby reducing the risk of electrostatic discharge. For example, in the packaging and storage of electronic products, antistatic plastics can prevent static electricity from damaging electronic components and ensure product reliability and performance; using antistatic plastics in flammable or explosive environments can reduce the risk of fire caused by static electricity.
[0004] The antistatic effect of existing antistatic plastics may decline with time and changes in the use environment. Especially in environments with high temperature and large humidity changes, the effect of antistatic additives may be reduced, thereby reducing the antistatic performance of plastics. At the same time, because the antistatic agents and other raw materials added may affect the recycling and reuse of plastics, how to prepare highly stable and renewable plastic particles has become a technical problem that needs to be solved urgently. Summary of the invention
[0005] The purpose of the present invention is to provide an antistatic renewable plastic particle to solve the technical problems existing in the above-mentioned background technology.
[0006] The technical solution of the present invention provides an antistatic renewable plastic particle, which comprises the following components in parts by weight: 100-125 parts of polyethylene, 35-80 parts of polypropylene, 100-130 parts of polyamide, 55-98 parts of octyl stearate, 65-87 parts of polycarbonate, 5-9 parts of antistatic agent, 3-8 parts of antioxidant, 12-20 parts of conductive filler, 8-13 parts of surfactant and 6-10 parts of conductive polymer.
[0007] In a preferred embodiment, the preparation process of the antistatic agent is as follows:
[0008] A1: 50 parts of stearic acid are dissolved, and 1.5 parts of 40% hydrochloric acid are added to the dissolved product, and then 25 parts of triethanolamine are added dropwise to the dissolved product through a constant temperature funnel, and then the temperature is raised to 150°C, and the temperature is kept at this temperature for dehydration for 2-3 hours to obtain a preform;
[0009] A2: The preform obtained in A1 is cooled to 55°C, 12 parts of isopropanol are added, and then 16 parts of dimethyl sulfate are added dropwise through a constant temperature funnel, stirred at high speed, and gradually heated to 85°C, reacted for 2-3 hours, and the solvent isopropanol is removed under reduced pressure. The sample is taken out and dried in a vacuum drying oven to obtain a biodegradable antistatic agent.
[0010] In a preferred embodiment, the dripping time of triethanolamine in A1 is 30-40 min, and the dripping time of dimethyl sulfate in A2 is 25-40 min.
[0011] In a preferred embodiment, the antioxidant is one or more of polyvinyl alcohol, polyethylene terephthalate, diphenylamine, butylated hydroxyanisole, and tert-butylhydroquinone.
[0012] In a preferred embodiment, the conductive filler is one or more of conductive fiber, manganese oxide, and indium tin oxide.
[0013] In a preferred embodiment, the surfactant is one or more of dimethyldiallylammonium chloride, polyvinyl fluoride, and polyether-modified siloxane.
[0014] In a preferred embodiment, the conductive polymer is one or more of polyaniline, polypyrrole, and polyaminostyrene.
[0015] A method for processing antistatic renewable plastic particles comprises the following steps:
[0016] S1: Take 100-125 parts of polyethylene, 35-80 parts of polypropylene, 100-130 parts of polyamide, 55-98 parts of octyl stearate, 65-87 parts of polycarbonate, 5-9 parts of antistatic agent, 3-8 parts of antioxidant, 12-20 parts of conductive filler, 8-13 parts of surfactant, and 6-10 parts of conductive polymer, put them into a blender and stir for 30-50 minutes;
[0017] S2: The original mixed and stirred ingredients are conveyed to the extruder through a conveying pipe, the extruded raw materials enter the cooling pool for cooling, the cooled raw materials are air-dried by an air dryer, the air-dried strip raw materials are cut and formed by a granulator, a filter is installed at the finished product outlet of the granulator to filter the particles that do not meet the requirements, the filtered particles are packaged to make finished products.
[0018] In a preferred embodiment, the temperatures of zone 1, zone 2, zone 3, zone 4, zone 5 and zone 6 of the extruder are 65°C, 70°C, 75°C, 80°C, 85°C and 90°C respectively.
[0019] The beneficial effects of the technical solution of the present invention are:
[0020] In this scheme, the preparation process of the antistatic agent is as follows: A1: dissolve 50 parts of stearic acid, add 1.5 parts of hydrochloric acid with a concentration of 40% to the dissolved product, and then drop 25 parts of triethanolamine to the dissolved product through a constant temperature funnel, then heat to 150°C, and keep dehydrating at this temperature for 2-3 hours to obtain a preform; A2: cool the preform obtained in A1 to 55°C, add 12 parts of isopropanol, and then drop 16 parts of dimethyl sulfate through a constant temperature funnel, stir at high speed, and gradually heat to 85°C, react for 2-3 hours, remove the solvent isopropanol under reduced pressure, take out the sample and dry it in a vacuum drying oven, and the biodegradable antistatic agent is obtained.
[0021] It can be seen from the experimental structure that after adding the antistatic agent prepared in this scheme, the prepared plastic particles have good antistatic properties, and their tensile strength and other properties are also relatively excellent, meeting the use requirements. In this scheme, the conductive filler can change the charge distribution on the plastic surface, and the conductive polymer material itself has conductivity, which can effectively reduce static electricity accumulation and further improve the antistatic performance. DETAILED DESCRIPTION
[0022] The present invention is further described in detail below. The embodiments of the present invention are provided for the purpose of illustration and description, and are not intended to be exhaustive or to limit the present invention to the disclosed forms. Many modifications and variations will be apparent to those of ordinary skill in the art. The embodiments are selected and described to better illustrate the principles and practical applications of the present invention, and to enable those of ordinary skill in the art to understand the present invention and design various embodiments with various modifications suitable for specific uses.
[0023] Example 1
[0024] The technical solution of the present invention provides an antistatic renewable plastic particle, comprising the following components in parts by weight: 100 parts of polyethylene, 35 parts of polypropylene, 100 parts of polyamide, 55 parts of octyl stearate, 65 parts of polycarbonate, 5 parts of antistatic agent, 3 parts of antioxidant, 12 parts of conductive filler, 8 parts of surfactant, and 6 parts of conductive polymer.
[0025] The preparation process of the antistatic agent is as follows:
[0026] A1: 50 parts of stearic acid are dissolved, and 1.5 parts of hydrochloric acid with a concentration of 40% is added to the dissolved product, and then 25 parts of triethanolamine is added dropwise to the dissolved product through a constant temperature funnel, and then the temperature is raised to 150°C, and the temperature is kept at this temperature for dehydration for 2 hours to obtain a preform;
[0027] A2: The preform obtained in A1 was cooled to 55°C, 12 parts of isopropanol were added, and then 16 parts of dimethyl sulfate were added dropwise through a constant temperature funnel. The mixture was stirred at high speed and gradually heated to 85°C. The reaction was continued for 2 hours. The solvent isopropanol was removed under reduced pressure, and the sample was taken out and dried in a vacuum drying oven to obtain a biodegradable antistatic agent.
[0028] The addition time of triethanolamine in A1 was 30 min, and the addition time of dimethyl sulfate in A2 was 2 min.
[0029] The antioxidant is polyvinyl alcohol. The conductive filler is conductive fiber. The surfactant is dimethyldiallyl ammonium chloride. The conductive filler can change the charge distribution on the plastic surface. The conductive polymer is polyaniline. The conductive polymer material itself has conductivity and can effectively reduce static electricity accumulation.
[0030] A method for processing antistatic renewable plastic particles comprises the following steps:
[0031] S1: Take 100 parts of polyethylene, 35 parts of polypropylene, 100 parts of polyamide, 55 parts of octyl stearate, 65 parts of polycarbonate, 5 parts of antistatic agent, 3 parts of antioxidant, 12 parts of conductive filler, 8 parts of surfactant, and 6 parts of conductive polymer, put them into a blender and stir for 30 minutes;
[0032] S2: The original mixed and stirred ingredients are conveyed to the extruder through a conveying pipe, the extruded raw materials enter the cooling pool for cooling, the cooled raw materials are air-dried by an air dryer, the air-dried strip raw materials are cut and formed by a granulator, a filter is installed at the finished product outlet of the granulator to filter the particles that do not meet the requirements, the filtered particles are packaged to make finished products.
[0033] The temperatures of zone 1, zone 2, zone 3, zone 4, zone 5 and zone 6 of the extruder are 65°C, 70°C, 75°C, 80°C, 85°C and 90°C respectively.
[0034] Example 2
[0035] The technical solution of the present invention provides an antistatic renewable plastic particle, comprising the following components in parts by weight: 125 parts of polyethylene, 80 parts of polypropylene, 130 parts of polyamide, 98 parts of octyl stearate, 87 parts of polycarbonate, 9 parts of antistatic agent, 8 parts of antioxidant, 20 parts of conductive filler, 13 parts of surfactant, and 10 parts of conductive polymer.
[0036] The preparation process of the antistatic agent is as follows:
[0037] A1: 50 parts of stearic acid were dissolved, and 1.5 parts of 40% hydrochloric acid were added to the dissolved product, and then 25 parts of triethanolamine were added dropwise to the dissolved product through a constant temperature funnel, and then the temperature was raised to 150°C, and the temperature was kept at this temperature for dehydration for 3 hours to obtain a preform;
[0038] A2: The preform obtained in A1 was cooled to 55°C, 12 parts of isopropanol were added, and then 16 parts of dimethyl sulfate were added dropwise through a constant temperature funnel. The mixture was stirred at high speed and gradually heated to 85°C. The reaction was continued for 3 hours. The solvent isopropanol was removed under reduced pressure, and the sample was taken out and dried in a vacuum drying oven to obtain a biodegradable antistatic agent.
[0039] The dropping time of triethanolamine in A1 was 40 min, and the dropping time of dimethyl sulfate in A2 was 40 min.
[0040] The antioxidant is polyethylene terephthalate, the conductive filler is manganese oxide, the surfactant is polyvinyl fluoride, and the conductive polymer is polypyrrole.
[0041] A method for processing antistatic renewable plastic particles comprises the following steps:
[0042] S1: Take 125 parts of polyethylene, 80 parts of polypropylene, 130 parts of polyamide, 98 parts of octyl stearate, 87 parts of polycarbonate, 9 parts of antistatic agent, 8 parts of antioxidant, 20 parts of conductive filler, 13 parts of surfactant, and 10 parts of conductive polymer, put them into a blender and stir for 50 minutes;
[0043] S2: The original mixed and stirred ingredients are conveyed to the extruder through a conveying pipe, the extruded raw materials enter the cooling pool for cooling, the cooled raw materials are air-dried by an air dryer, the air-dried strip raw materials are cut and formed by a granulator, a filter is installed at the finished product outlet of the granulator to filter the particles that do not meet the requirements, the filtered particles are packaged to make finished products.
[0044] The temperatures of zone 1, zone 2, zone 3, zone 4, zone 5 and zone 6 of the extruder are 65°C, 70°C, 75°C, 80°C, 85°C and 90°C respectively.
[0045] Example 3
[0046] The technical solution of the present invention provides an antistatic renewable plastic particle, comprising the following components in parts by weight: 110 parts of polyethylene, 50 parts of polypropylene, 120 parts of polyamide, 65 parts of octyl stearate, 72 parts of polycarbonate, 6 parts of antistatic agent, 5 parts of antioxidant, 15 parts of conductive filler, 10 parts of surfactant, and 8 parts of conductive polymer.
[0047] The preparation process of the antistatic agent is as follows:
[0048] A1: 50 parts of stearic acid are dissolved, and 1.5 parts of hydrochloric acid with a concentration of 40% is added to the dissolved product, and then 25 parts of triethanolamine is added dropwise to the dissolved product through a constant temperature funnel, and then the temperature is raised to 150°C, and the temperature is kept at this temperature for dehydration for 2 hours to obtain a preform;
[0049] A2: The preform obtained in A1 was cooled to 55°C, 12 parts of isopropanol were added, and then 16 parts of dimethyl sulfate were added dropwise through a constant temperature funnel. The mixture was stirred at high speed and gradually heated to 85°C. The reaction was continued for 2 hours. The solvent isopropanol was removed under reduced pressure, and the sample was taken out and dried in a vacuum drying oven to obtain a biodegradable antistatic agent.
[0050] The addition time of triethanolamine in A1 was 30 min, and the addition time of dimethyl sulfate in A2 was 25 min.
[0051] The antioxidant is a mixture of diphenylamine and butylated hydroxyanisole. The conductive filler is indium tin oxide. The surfactant is polyether modified siloxane. The conductive polymer is polyaminostyrene.
[0052] A method for processing antistatic renewable plastic particles comprises the following steps:
[0053] S1: Take 110 parts of polyethylene, 50 parts of polypropylene, 120 parts of polyamide, 65 parts of octyl stearate, 72 parts of polycarbonate, 6 parts of antistatic agent, 5 parts of antioxidant, 15 parts of conductive filler, 10 parts of surfactant, and 8 parts of conductive polymer, put them into a blender and stir for 40 minutes;
[0054] S2: The original mixed and stirred ingredients are conveyed to the extruder through a conveying pipe, the extruded raw materials enter the cooling pool for cooling, the cooled raw materials are air-dried by an air dryer, the air-dried strip raw materials are cut and formed by a granulator, a filter is installed at the finished product outlet of the granulator to filter the particles that do not meet the requirements, the filtered particles are packaged to make finished products.
[0055] The temperatures of zone 1, zone 2, zone 3, zone 4, zone 5 and zone 6 of the extruder are 65°C, 70°C, 75°C, 80°C, 85°C and 90°C respectively.
[0056] Example 4
[0057] The technical solution of the present invention provides an antistatic renewable plastic particle, comprising the following components in parts by weight: 110 parts of polyethylene, 55 parts of polypropylene, 100 parts of polyamide, 85 parts of octyl stearate, 80 parts of polycarbonate, 7 parts of antistatic agent, 6 parts of antioxidant, 13 parts of conductive filler, 9 parts of surfactant, and 6 parts of conductive polymer.
[0058] The preparation process of the antistatic agent is as follows:
[0059] A1: 50 parts of stearic acid were dissolved, and 1.5 parts of 40% hydrochloric acid were added to the dissolved product, and then 25 parts of triethanolamine were added dropwise to the dissolved product through a constant temperature funnel, and then the temperature was raised to 150°C, and the temperature was kept at this temperature for dehydration for 3 hours to obtain a preform;
[0060] A2: The preform obtained in A1 was cooled to 55°C, 12 parts of isopropanol were added, and then 16 parts of dimethyl sulfate were added dropwise through a constant temperature funnel. The mixture was stirred at high speed and gradually heated to 85°C. The reaction was continued for 3 hours. The solvent isopropanol was removed under reduced pressure, and the sample was taken out and dried in a vacuum drying oven to obtain a biodegradable antistatic agent.
[0061] The dropping time of triethanolamine in A1 was 40 min, and the dropping time of dimethyl sulfate in A2 was 40 min.
[0062] The antioxidant is a mixture of polyvinyl alcohol and polyethylene terephthalate. The conductive filler is conductive fiber. The surfactant is dimethyldiallyl ammonium chloride. The conductive polymer is polyaminostyrene.
[0063] A method for processing antistatic renewable plastic particles comprises the following steps:
[0064] S1: Take 110 parts of polyethylene, 55 parts of polypropylene, 100 parts of polyamide, 85 parts of octyl stearate, 80 parts of polycarbonate, 7 parts of antistatic agent, 6 parts of antioxidant, 13 parts of conductive filler, 9 parts of surfactant, and 6 parts of conductive polymer, put them into a blender and stir for 30-50 minutes;
[0065] S2: The original mixed and stirred ingredients are conveyed to the extruder through a conveying pipe, the extruded raw materials enter the cooling pool for cooling, the cooled raw materials are air-dried by an air dryer, the air-dried strip raw materials are cut and formed by a granulator, a filter is installed at the finished product outlet of the granulator to filter the particles that do not meet the requirements, the filtered particles are packaged to make finished products.
[0066] The temperatures of zone 1, zone 2, zone 3, zone 4, zone 5 and zone 6 of the extruder are 65°C, 70°C, 75°C, 80°C, 85°C and 90°C respectively.
[0067] Comparative Example 1
[0068] Another antistatic agent 1 purchased from the market was added, and the rest was the same as in Example 1.
[0069] Comparative Example 1
[0070] Another antistatic agent 2 purchased from the market was added, and the rest was the same as in Example 1.
[0071] The plastic particles prepared by implementing 1-4 are prepared into plastic products by the following steps: the prepared particles are ground by a grinding machine, and then the ground powder is sucked by the plastic suction machine and melted by heating to 180°C, and the melted plastic water is injected into a mold of the corresponding shape by an injection molding machine, the temperature is maintained at 120°C, the pressure is 4MPa, and maintained for 1min, and then quickly cooled to room temperature, and the plastic product is taken out from the mold. Then the performance test is carried out, and the results are shown in Table 1:
[0072] Table 1
[0073]
[0074] It can be seen from the experimental structure that after adding the antistatic agent prepared in this scheme, the prepared plastic particles have good antistatic properties, and their tensile strength and other properties are also relatively excellent, meeting the use requirements. In this scheme, the conductive filler can change the charge distribution on the plastic surface, and the conductive polymer material itself has conductivity, which can effectively reduce static electricity accumulation and further improve the antistatic performance.
[0075] Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field and related fields without creative work should fall within the scope of protection of the present invention. The structures, devices and operating methods not specifically described and explained in the present invention are implemented according to the conventional means in the field unless otherwise specified and limited.
Claims
1. An antistatic renewable plastic particle, characterized in that: The invention comprises the following components in parts by weight: 100-125 parts of polyethylene, 35-80 parts of polypropylene, 100-130 parts of polyamide, 55-98 parts of octyl stearate, 65-87 parts of polycarbonate, 5-9 parts of antistatic agent, 3-8 parts of antioxidant, 12-20 parts of conductive filler, 8-13 parts of surfactant and 6-10 parts of conductive polymer.
2. The antistatic renewable plastic particles according to claim 1, characterized in that: The preparation process of the antistatic agent is as follows: A1: 50 parts of stearic acid are dissolved, and 1.5 parts of 40% hydrochloric acid are added to the dissolved product, and then 25 parts of triethanolamine are added dropwise to the dissolved product through a constant temperature funnel, and then the temperature is raised to 150°C, and the temperature is kept at this temperature for dehydration for 2-3 hours to obtain a preform; A2: The preform obtained in A1 is cooled to 55°C, 12 parts of isopropanol are added, and then 16 parts of dimethyl sulfate are added dropwise through a constant temperature funnel, stirred at high speed, and gradually heated to 85°C, reacted for 2-3 hours, and the solvent isopropanol is removed under reduced pressure. The sample is taken out and dried in a vacuum drying oven to obtain a biodegradable antistatic agent.
3. The antistatic renewable plastic particles according to claim 1, characterized in that: The dropping time of triethanolamine in A1 is 30-40 min, and the dropping time of dimethyl sulfate in A2 is 25-40 min.
4. The antistatic renewable plastic particles according to claim 1, characterized in that: The antioxidant is one or more of polyvinyl alcohol, polyethylene terephthalate, diphenylamine, butylated hydroxyanisole, and tert-butylhydroquinone.
5. The antistatic renewable plastic particles according to claim 1, characterized in that: The conductive filler is one or more of conductive fiber, manganese oxide, and indium tin oxide.
6. The antistatic renewable plastic particles according to claim 1, characterized in that: The surfactant is one or more of dimethyldiallylammonium chloride, polyvinyl fluoride, and polyether-modified siloxane.
7. The antistatic renewable plastic particles according to claim 1, characterized in that: The conductive polymer is one or more of polyaniline, polypyrrole and polyaminostyrene.
8. A method for processing antistatic renewable plastic particles according to any one of claims 1 to 7, characterized in that: The steps include: S1: Take 100-125 parts of polyethylene, 35-80 parts of polypropylene, 100-130 parts of polyamide, 55-98 parts of octyl stearate, 65-87 parts of polycarbonate, 5-9 parts of antistatic agent, 3-8 parts of antioxidant, 12-20 parts of conductive filler, 8-13 parts of surfactant, and 6-10 parts of conductive polymer, put them into a blender and stir for 30-50 minutes; S2: The original mixed and stirred ingredients are conveyed to the extruder through a conveying pipe, the extruded raw materials enter the cooling pool for cooling, the cooled raw materials are air-dried by an air dryer, the air-dried strip raw materials are cut and formed by a granulator, a filter is installed at the finished product outlet of the granulator to filter the particles that do not meet the requirements, the filtered particles are packaged to make finished products.
9. The method for processing antistatic renewable plastic particles according to claim 8, characterized in that: The temperatures of zone 1, zone 2, zone 3, zone 4, zone 5 and zone 6 of the extruder are 65°C, 70°C, 75°C, 80°C, 85°C and 90°C respectively.
